Value Co-creation in Online Shopping - Branisso, Diana Sinclair; Rocha-Freire, Roberta; Hor-Meyll, Luis Fernando (Revista ADM.MADE, 2020)
<span style="font-size: 11.0pt; line-height: 107%; font-family: ";Calibri";,sans-serif; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: ";Times New Roman";; mso-hansi-theme-font: minor-latin; mso-bidi-theme-font: minor-latin; mso-ansi-language: EN-US; mso-fareast-language: PT-BR; mso-bidi-language: AR-SA;" lang="EN-US">This research presents a critical analysis of value co-creation in online shopping, based on a decade of academic marketing literature. It was carried out with quantitative - bibliometric and bibliographic - and qualitative content analysis. The identification of main theories, paradigms and constructs, as well as research cliques, helps in establishing the theoretical framework necessary for an incipient research field such as this. The analysis identified four main research lines: customers as co-creators within the interaction with companies; customer-employee co-creation issues; customers" interaction with other clients resulting in co-creation; and the impacts of social network resources in online shopping behavior. A discerning factor regarding co-creation in online settings is that the advances of technology empowered consumers. Besides, customer co-creation is at the core of online shopping innovations. The interactivity provided by the online shopping setting is ideal for value co-creation to flourish. Nevertheless, this is still a new research area, whose studies are scarce. Understanding the latest advances of value co-creation in online shopping, and what lies ahead of it, is essential in grasping the digital commerce structure in the service logic era.